Analisis Penyusunan Laporan Keuangan UMKM pada CV Mitra Arsitek (Studi Kasus Pasaman Barat) - Faiza Saputri; Dewi Manda Anggraini (Lembaga Yasin AlSys, 2026)
Although the preparation of financial statements based on the Financial Accounting Standards for Micro, Small, and Medium Entities (SAK EMKM) plays an important role in improving the accountability and quality of financial management among micro, small, and medium enterprises (MSMEs), research on their implementation at CV Mitra Arsitek in West Pasaman Regency remains limited. This study aimed to analyze the preparation of financial statements at CV Mitra Arsitek based on SAK EMKM and to identify the challenges encountered in its implementation. This study employed a qualitative approach with a field research and case study design. Data were obtained from one key informant selected through purposive sampling. Data were collected through observation, semi-structured interviews, and documentation and were subsequently analyzed using an interactive analysis model comprising data reduction, data display, and conclusion drawing. The results showed that financial statements at CV Mitra Arsitek were still prepared in a simple manner by recording cash receipts and disbursements and therefore did not yet comply with SAK EMKM requirements. The company had not prepared a general journal, general ledger, statement of financial position, income statement, or notes to the financial statements. The main challenges in implementing SAK EMKM included limited understanding of accounting standards, the absence of human resources competent in accounting, and the use of a manual recording system. This study emphasizes the need to improve understanding, human resource competence, and financial recording systems so that the company’s financial reporting complies with SAK EMKM. The findings provide practical implications for CV Mitra Arsitek in evaluating and improving the quality of its financial reporting and enrich the literature on the implementation of accounting standards among MSMEs.